2023
DOI: 10.1002/adfm.202303667
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Solvent‐Coupled Anion‐Derived Interphase to Stabilize Silicon Microparticle Anodes for High‐Energy‐Density Batteries

Abstract: Si microparticle (SiMP) anodes feature much lower production cost and higher tap density compared to their nanosized counterparts, which hold great promise for high‐energy‐density lithium‐ion batteries, yet they suffer from unavoidable particle pulverization during repeated cycling, thus making their practical application extremely challenging. Herein, a non‐flammable localized high‐concentration electrolyte (LHCE) is rationally formulated using a fluorinated solvent, 2,2,2‐trifluoroethyl methyl carbonate (FEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…18–20 Nevertheless, most fluorinated solvents suffer from a decline in Li-ion conductivity due to their weakened Li-ion solvation. 15,21–23 It was demonstrated that when small molecule ether solvents were partially fluorinated via introducing –CF 2 – in the middle of the ether chain, the coordination/dissociation of Li ions in these solvents becomes easy, leading to good Li-ion conductivity and high oxidation stability, as reported by Cui and colleagues. 24–26 Ali Coskun et al modified the ether solvent into a cyclic structure with –CF 3 as the substituent groups, which could achieve a high voltage stability and retain the solvation ability of oxygen atoms.…”
Section: Introductionmentioning
confidence: 78%
“…18–20 Nevertheless, most fluorinated solvents suffer from a decline in Li-ion conductivity due to their weakened Li-ion solvation. 15,21–23 It was demonstrated that when small molecule ether solvents were partially fluorinated via introducing –CF 2 – in the middle of the ether chain, the coordination/dissociation of Li ions in these solvents becomes easy, leading to good Li-ion conductivity and high oxidation stability, as reported by Cui and colleagues. 24–26 Ali Coskun et al modified the ether solvent into a cyclic structure with –CF 3 as the substituent groups, which could achieve a high voltage stability and retain the solvation ability of oxygen atoms.…”
Section: Introductionmentioning
confidence: 78%
“…On the other hand, the O 1s spectrum in Figure S20b reveals oxygen-rich organic SEI components, such as the carbonyl group (C�O), RCO 2 Li, and polyether carbon (−(CH 2 − CH 2 −O) n −), on the silicon anode in the LE, which may mainly arise from the solvent decomposition. In addition, some S-containing species, such as Li 2 S, Li x S, S−N, SO 2 F, and RSO 3 , 56 and the B-containing species like B−O and B−F species exist in the SEI of Si electrodes cycled in the QSGPE or in the LE. Figure 6c shows a schematic representation of the SEI related to the QSGPE with the F, N-rich inorganic/organic hybrid structure, mainly including polymers, LiF, and Li 3 N as well as small amounts of S-and B-based compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The first class of novel electrolytes is formulated by LiPF 6 and high voltage stable solvents with different functional groups (Scheme 2 and Table 2), such as sulfolane (SL), [97] FEC, [97,[99][100][101][102][103][104][105][106][107] 2,2,2-trifluoroethyl acetate (TFA), [98,106] acetonitrile (AN), [99][100] methyl difluoroacetate (MDFA), [102] ethoxypentafluoro-cyclotriphosphazene (PFPN), [102] 2,2,2-trifluoroethyl methyl carbonate (FEMC), [103][104][105] 1,1,2,2-tetrafluoroethyl-2′,2′,2′trifluoroethyl ether (HFE). [103][104] Solvents with different functional groups endow novel electrolytes with various characteristics.…”
Section: Medium/low Concentration Electrolytes For High-ni Libsmentioning
confidence: 99%